Building Anti-Corruption Character from School Level - Assyifa, Dzakirah Nur; Indriyani, Sri; Safitri, Elsa; Gimri, Farhah Desrianty; Ardiansyah, Bambang; Matang, Matang (Jurnal Edukasi Terkini, 2025)
Purpose - This study aims to analyze the importance of anti-corruption education as a strategic step to shape students' awareness and character from an early age, with the aim of introducing actions that include or have the potential to become corruption and building integrity through comprehensive character education. Methodology/Design/Approach - This study uses a content analysis method as a qualitative approach, namely by analyzing and interpreting data in the form of texts or documents containing information related to anti-corruption education, such as curriculum, teaching materials, or activity records at school. The findings of this study show how anti-corruption values ​​are integrated into the learning process and the role of teachers as agents of change in shaping students' character. Originality/Value - By integrating anti-corruption education, moral values, and the sustainability of daily practices, schools can create a culture that rejects corruption, thus forming a young generation with integrity, responsibility, and is ready to build a cleaner and fairer future.